The Japanese health care system-based cost-effectiveness of photodynamic diagnosis-assisted transurethral resection of bladder tumor for non-muscle invasive bladder cancer. (30th December 2022) - Nishimura, Nobutaka; Miyake, Makito; Miyamoto, Tatsuki; Tomizawa, Mitsuru; Shimizu, Takuto; Morizawa, Yosuke; Hori, Shunta; Gotoh, Daisuke; Nakai, Yasushi; Torimoto, Kazumasa; Tanaka, Nobumichi; Fujimoto, Kiyohide
Abstract: Background: Photodynamic diagnosis-assisted transurethral resection of bladder tumor reduces the risk of intravesical recurrence compared with conventional white light-transurethral resection of bladder tumor. However, the patient burden of costs for photodynamic diagnosis-transurethral resection of bladder tumor is higher than that for white light-transurethral resection of bladder tumor per installment, and the impact of the medical economics of photodynamic diagnosis-transurethral resection of bladder tumor is unclear. Therefore, we evaluated the Japanese health care system-based cost-effectiveness of photodynamic diagnosis-transurethral resection of bladder tumor compared with that of white light-transurethral resection of bladder tumor. Methods: We conducted a retrospective chart review of 100 patients who underwent initial white light- or photodynamic diagnosis-transurethral resection of bladder tumor for non-muscle invasive bladder cancer from February 2012 to August 2019. Cumulative intravesical recurrences during 1000 post-operative days after the initial transurethral resection of bladder tumor were counted. Furthermore, the cumulative costs were calculated using the Diagnostic Procedure Combination and Per-Diem Payment System unique to Japan. The costs/year/person calculated using the person-year method was compared between the white light- and photodynamic diagnosis-transurethral resection of bladder tumor. Results: Among the 100 patients, 40 (40%) and 60 (60%) underwent the initial white light- and photodynamic diagnosis-transurethral resection of bladder tumor, respectively. The cumulative incidence of bladder recurrence requiring hospitalization and transurethral resection of bladder tumor was 20 and 5% for the white light-transurethral resection of bladder tumor and photodynamic diagnosis-transurethral resection of bladder tumor, respectively. The costs for hospitalization and surgical procedures per white light- or photodynamic diagnosis-transurethral resection of bladder tumor were 348 228 and 481 820 Japanese yen, respectively. The cost/year/person by the person-year method was 8073 and 8557 Japanese yen for the white light- and photodynamic diagnosis-transurethral resection of bladder tumor, respectively. Conclusions: The cost/year/person for hospitalization and surgical procedures was slightly different between the white light- and photodynamic diagnosis-transurethral resection of bladder tumor. Furthermore, photodynamic diagnosis-transurethral resection of bladder tumor can reduce intravesical recurrence and is more cost-effective than white light-transurethral resection of bladder tumor. Abstract : We evaluated the Japanese health care system-based cost-effectiveness of photodynamic diagnosis-assisted transurethral resection of bladder tumor compared with white light-transurethral resection of bladder tumor. Photodynamic diagnosis-transurethral resection of bladder tumor was more cost-effective than the conventional white light-transurethral resection of bladder tumor.